CHARACTERISTICS PHYSICAL PROPERTIES OF SOIL FOR CONSERVATION POND PLANNING IN KECAMATAN LIANG ANGGANG PEATLANDS - Rusliansyah, Rusliansyah; Rusdiansyah, Rusdiansyah; Ma’ruf, Muhammad Afief; Santoso, Meilinda Ayunita (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2017)
Peatland fires in 2015 that hit 23 of 33 provinces in Indonesia is one of the worst fires in history. South Kalimantan is one of the 23 provinces with the burned land area of 19.179,9 hectares. Peatland burning in Banjarbaru and of Banjar Regency which totaled 1.536 fire point burning with a land area of approximately 1.500 hectares. The main factor of this land fires is of decreased water level in the peat land. Therefore, to overcome that fires will not happen again by creating a conservation pond to hold water, especially during the rainy season in order to keep moist peat. The planning an peat land conservation in this area of 900 hectares. Peat ecosystem restoration can be done through the realignment of hydrological function where peat dome as a long-term water storage. The purpose of the research is to knowing the state of the physical properties soil for conservation pond made and knowing the condition of the ground water level in the field. From the results of an investigation soil physical properties obtained peat has not undergone recast and the number of pores in the soil are very large so that the soil becomes porous with a high water level conditions.